2012
DOI: 10.1537/ase.100925
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative changes of the spine in people from prehistoric Okhotsk culture and two ancient human groups from Kanto and Okinawa, Japan

Abstract: Degenerative changes of the spine in people of the Okhotsk culture were investigated in adult human skeletal remains from 38 males and 34 females. These findings were then compared with those in materials obtained from the medieval Kamakura period and early-modern peasants on Kumejima, Ryukyu Islands. The three samples clearly showed different patterns. In the Okhotsk series, the cervical spine of each sex had most osteophytes on the vertebral body, while the Kumejima samples had the highest frequency on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
(84 reference statements)
2
14
0
Order By: Relevance
“…This relationship is also supported by the results of recent mitochondrial DNA analyses (Sato et al, 2007(Sato et al, , 2009. Severe degenerative changes and compression fractures were found in the spines and limb bones of these remains, probably due to the heavy loads associated with marine mammal hunting and fishing Shimoda et al, 2012;Suzuki et al, 2016).…”
Section: Introductionsupporting
confidence: 67%
“…This relationship is also supported by the results of recent mitochondrial DNA analyses (Sato et al, 2007(Sato et al, , 2009. Severe degenerative changes and compression fractures were found in the spines and limb bones of these remains, probably due to the heavy loads associated with marine mammal hunting and fishing Shimoda et al, 2012;Suzuki et al, 2016).…”
Section: Introductionsupporting
confidence: 67%
“…Oxenham and Matsumura (2008) compared the oral and physiological well-being of the Okhotsk people with other hunter-gatherer populations in Arctic regions and found that oral health profiles are sensitive to subsistence strategies among cold-adapted populations. Shimoda et al (2012) examined degenerative changes of the spine in the Okhotsk people and found that severe osteophytes on the body of the lumbar vertebrae were more frequently detected in the Okhotsk males. They concluded that, because they developed a considerable maritime infrastructure, the lifestyle required for sea-mammal hunting and fishing seems to have particularly affected the incidence of severe degenerative changes of the lumbar vertebrae.…”
Section: Methodsmentioning
confidence: 99%
“…The first author of this paper (T.N.) and colleagues analyzed them and indicated several new findings regarding paleodemography and paleopathology of the medieval Japanese: (1) the paleodemographic study of the YM and YCSB-372 series demonstrated a higher proportion of deaths in young individuals than the Edo period (1603-1867 AD) Japanese and implied severe living conditions in medieval Kamakura due to malnutrition and warfare (Nagaoka et al, 2006;; (2) the paleopathological study of the YM site revealed the first evidence for leprosy and tuberculosis in medieval Japan (Hirata et al, 2011) and less frequent degenerative changes in spines than the Okhotsk and Kumejima skeletal series (Shimoda et al, 2012); and (3) the presence of cut marks on the crania from the Seiyokan, YM, and YCSB-372 sites strongly suggested the prevalence of violence in medieval Japan (Hirata et al, 2004;Nagaoka et al, 2009Nagaoka et al, , 2010. These studies have revealed the life and death situations of the urban inhabitants of medieval Japan from multiple perspectives and a tentative hypothesis is that the medieval people suffered from poor health due to malnutrition and interpersonal violence.…”
Section: Introductionmentioning
confidence: 99%